The Social Consequences of War Captivity in the Late Middle Ages - Niewiński, Andrzej (Social consequences of war, 2024)
The article addresses the issue of military captivity as a social phenomenon structured in terms of relationships, as it inevitably involves both sides of the conflict: those who fell into captivity, but also those who became owners of the captives. Added to this are the relationships with those who were (legally or customarily) obliged to try to free the captives. Throughout the Middle Ages, only in the Iberian Peninsula did the legal regulation of the prisoner of war evolve. The peculiarities of warfare and mutual contacts between Christians and Muslims determined this. The Crusades and closer contact with the Muslim world also contributed to an increased sensitivity to the fate of prisoners of war, which was reflected in the institutionalisation of the procedure for their release. Captivity had an important economic dimension, linked to the extraction of ransom money. The raising of funds for ransom rested primarily on the captive and his family, which often had very serious social repercussions.